Pengaruh Sektor Pariwisata Terhadap Perekonomian Masyarakat dan Kebersihan Lingkungan (Studi Kasus : Pantai Grand Elty Krakatoa Resort Kalianda, Lampung Selatan) - hilda kholailah; Septi wulandari; Rossi Lara Murtiningsih (Fakultas Ekonomi Universitas Bangka Belitung, 2021)
Abstract Tourism is an industry that is growing rapidly every year. In Indonesia, the tourism sector is developed as a sector that promises to bring in income for the state, especially in areas that have natural resources, as well as abundant cultural resources. Various potentials are explored to attract tourists to come to visit so that they can expect to be able to improve the welfare of the community. The purpose of this research is to identify the potential of natural resources that can be utilized. The object to be identified or analyzed is the beach at Grand Elty Krakatoa Resort Kalianda, South Lampung. By using a descriptive approach research method with interview techniques that can be used to obtain more relevant and precise information from the informants. Keywords: Tourism, Tourists, Natural Resources Potential